Ethical Sensitivity and Moral Considerations of Accounting Students Based on Accounting Ethics Education - Budi Astuti; Witri Gustina; Rina Yuniarti; Yusmaniarti Yusmaniarti; Nensi Yuniarti Zs (Syntax Corporation Indonesia, 2021)
The purpose of this study was to examine the differences in ethical sensitivity and moral considerations of students based on semester and gender. The population of this study was Accounting Students at the University of Muhammadiyah Bengkulu. Sampling using the purposive sampling method to obtain as many as 87 respondents. The method of data collection is the questionnaire method. The data analysis technique used descriptive statistical analysis, data quality test, and hypothesis testing. The result of this research is that there is no difference between the ability of students who have received accounting ethics education in identifying ethical dilemmas compared to the ability of students who have not received accounting ethics education. The ability of female students who have received accounting ethics education is higher in identifying ethical dilemmas than the ability of male students. The ability of students who have received accounting ethics education is higher in making moral judgments than the ability of students who have not received accounting ethics education. There is no difference between the ability of female students who have received accounting ethics education better in making moral judgments than the ability of male students.